Electric Train Application Study For Catenary-PantographInteraction - Parlakyıldız, Sakır; Gençoğlu, Muhsin Tunay; Cengiz, Mehmet Sait (My University, 2020)
Today, electric rail systems that use clean energy and are a fast and reliable means of transportation are used more because of theirefficiency. The main purpose of new studies investigating pantograph catenary interaction in Electric Rail Systems is to detectmalfunctions. With the spread of high-speed trains in electric rail systems, malfunctions occur in pantograph and catenary systemsoperating under high current and high voltage. The contact force of the pantograph-catenary system erodes the pantograph surface andarcs occur. For this reason, periodic control is mandatory in pantograph-catenary systems. In this study, new, effective, sensitive, stable,real-time applicable and contactless condition monitoring, analysis, control, and diagnostic methods were investigated for pantograph catenary systems that provide energy transmission from the electric line to the locomotive in electric trains. A literature search and studyapplication after has been carried out for modeling a pantograph-catenary system and analysis of system parameters, instantaneouscontrol of the contact force between the pantograph and catenary to diagnose malfunctions in the pantograph-catenary system. It hasbeen observed that pantograph-catenary interaction is negatively affected and the quality of energy transmission decreases if the systemparameters change for any reason. In pantograph-catenary systems, the importance of periodic pantograph control, which will ensurethe stable and efficient operation of the system, is understood if the parameters change. Because changes in parameters causemalfunctions. Therefore, periodic control and continuous monitoring of the system is required.
Keywords: Mühendislik; Elektrik ve Elektronik; Mühendislik; Makine